Copper Hexacyanoferrate-Based Sensor For Anodicdetermination Of Paracetamol In Pure Form And In Pharmaceutical Tablets - R.A. KALAIVANI; S. SRIMAN NARAYANAN (International Journal of Pharma and Bio Sciences, 2012)
Paracetamol (Acetaminophen) is one of the most frequently used analgesic drugs. At therapeutic dosage levels the drug is relatively non-toxic. Because of its increasing therapeutic use, its assay and quality control are of vital importance. A number of methods, including instrumental and titrimetric are available for the quantitative determination of paracetamol in literature. A simple and accurate sol-gel method has been developed for the assay of paracetamol in pure form and in tablets using Copper hexacyanoferrate (CuHCF) modified carbon ceramic composite electrode. The electrode was characterized using voltammetric techniques and its electrocatalytic activity for the oxidation of paracetamol was also studied. The carbon composite electrode has the advantage of sensing paracetamol at a lower potential and with a higher sensitivity. The results obtained using the modified electrode was applied for the determination of paracetomol in commercially available tablets. The results obtained reveal that the electrode under study could be used as an effective sensor for online monitoring of paracetomol.